Preparation of High Modulus Poly(Ethylene Terephthalate): Influence of Molecular Weight, Extrusion, and Drawing Parameters. (26th January 2017) - Zhang, Jian Min; Hua, Qingsong; Reynolds, Christopher T.; Zhao, Yuling; Dai, Zuoqiang; Bilotti, Emiliano; Tang, Jie; Peijs, Ton
Abstract : Poly(ethylene terephthalate) (PET) which is one of the most commercially important polymers, has for many years been an interesting candidate for the production of high performance fibres and tapes. In current study, we focus on investigating the effects of the various processing variables on the mechanical properties of PET produced by a distinctive process of melt spinning and uniaxial two-stage solid-state drawing (SSD). These processing variables include screw rotation speed during extrusion, fibre take-up speed, molecular weight, draw-ratio, and drawing temperature. As-spun PET production using a single-screw extrusion process was first optimized to induce an optimal polymer microstructure for subsequent drawing processes. It was found that less crystallization which occurred during this process would lead to better drawability, higher draw-ratio, and mechanical properties in the subsequent SSD process. Then the effect of drawing temperature (DT) in uniaxial two-stage SSD process was studied to understand how DT (<T g or close to T g or close to T r e c ) would affect the crystallization, draw-ratio, and final mechanical properties of PET. The designed process in current work is simulated to an industrial production process for PET fibres; therefore, results and analysis in this paper have significant importance for industrial production.